"'Foul, strange and unnatural': Poison as a murder weapon in English Renaissance drama" - Sadowski, Piotr (My University, 2020)
Less spectacular than theatrical violence involving bloodshed, stage murder by poison is nonetheless unsettling because of its secretive nature. Perceived in Renaissance England as dishonorable and unmanly, poison was often associated with women as the “weaker” sex, with discriminated minorities such as Jews, and with Machiavellian politics from continental Europe.
PUBLISHED
Keywords: Renaissance England; Theatre; Drama; Poison; Murder; Immunology, Inflammation & Infection; Manuscript, Book and Print Cultures; Gender studies; History; Literature